2019
DOI: 10.1186/s12903-019-0977-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of casein phosphopeptide-amorphous calcium phosphate on remineralization of white spot lesions in vitro and clinical research: a systematic review and meta-analysis

Abstract: BackgroundThis systematic review with meta-analyses sought to answer whether casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) provided a remineralizing benefit superior to that of nonintervention or placebo.MethodsFollowing Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines, Cochrane databases, PubMed, EmBase, and Ovid up to May 20th, 2019, were scanned, only published in English. Study information extraction and methodological quality assessments were accomplishe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 40 publications
2
30
0
1
Order By: Relevance
“…Previous clinical and laboratory studies focused on the effectiveness of TMP in preventing and reversing of early dental caries lesions [ 10 14 ]. Meta-analyses of clinical studies have also been published to support the use of the product [ 11 – 22 ]. However, no other study has addressed regular users’ views about the product, how the product performs and addresses their individual needs (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical and laboratory studies focused on the effectiveness of TMP in preventing and reversing of early dental caries lesions [ 10 14 ]. Meta-analyses of clinical studies have also been published to support the use of the product [ 11 – 22 ]. However, no other study has addressed regular users’ views about the product, how the product performs and addresses their individual needs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high-level of evidence supporting the ability of CPP-ACP to remineralise early caries lesions and prevent their progression [ 10 14 ]. There are now twelve published systematic meta-analyses of these clinical studies to support the use of CPP-ACP to lower caries risk [ 11 – 22 ]. In addition, CPP-ACP effectiveness has also been demonstrated in relation to the reduction of cariogenic bacteria and increased colonization of commensal microorganisms, and the reduction of dentine hypersensitivity [ 23 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation showed significant heterogenicity in the surface hardness values, due to which a random model of analysis was performed which included 5 of the 8 studies selected and which showed values (SMD = 1.19, 95% CI: [0.72, 1.66], p < 0.00001) indicating that the use of CPP-ACP resulted in superior remineralisation. The atomic force microscopy (AFM) analysis of three of their studies also showed that CPP-ACP's use resulted in reduced roughness of the enamel surface and showed their ability to repair and form a smooth surface [14,15]. In another study by Fernando et al which described the use of SnF2 along with ACP-CCP to induce tooth repair, their in-vitro studies showed the ability of SnF2 to interact with CPP-ACP complexes to form a nanofilament coating on the tooth surface, with superior remineralisation activity in comparison to either of these materials individually.…”
Section: Enamel Surface Mineralisationmentioning
confidence: 98%
“…Most of them include the use of fluoridated toothpastes and other fluoride-containing products like varnishes and mouthwashes. Casein phosphopeptide (CPP)-amorphous calcium phosphate (ACP) combinations are used for improving enamel surface remineralisation owing to their ability to stabilise calcium, phosphate, and fluoride ions, which are already available in saliva, leading to faster and better surface remineralisation of the enamel layer [14]. Ma et al (2019) conducted a systematic review with metanalyses describing the efficiency of CCP-ACP in enamel remineralisation.…”
Section: Enamel Surface Mineralisationmentioning
confidence: 99%
See 1 more Smart Citation